Functional Diversity of Mycorrhiza and Sustainable Agriculture - Management to Overcome Biotic and Abiotic Stresses - Goss, M.J. (2017)
The current world population of 7.5 billion is expected to be 20% greater by 2050 and so we have little over 33 years to ensure the means of producing sufficient food to meet the expected demand. One of the options that previously were available to us for expanding world production of cereals, vegetables, fruits, and meat, namely bringing more land into production, is no longer possible and consequently we must everywhere increase the productivity of the land. But this time we must not attempt it without making every effort to safeguard the environment. Put in a slightly different way, we have to grow more but conserve the soil and its biodiversity, be more efficient in terms of water use, improve nutrient-use efficiency so that fewer applied nutrients end up contaminating our freshwater and eutrophying our lakes and shallow seas or adversely affecting the quality of our air and contributing to the atmospheric loading of greenhouse gases. If we add in a desire to reduce the application of pesticides, especially those targeting root pathogens, it would seem to represent an extremely challenging task. Perhaps it will be a surprise to some that the answer to many of these challenges might well be one result of the development of techniques that allow us to determine the make-up of microorganisms, which has had huge impacts on soil science and its application in agronomy. Beginning with the ability to differentiate the fatty acid and phospholipid profiles of microbial communities in soil and reaching the current status, where the whole genetic code of an organism can be determined, the previously rather opaque world of soil microbiology is being clarified at an unprecedented rate. From around the time that the word mycorrhiza was coined by Frank in 1885, mycorrhizal fungi have been of interest because of their special relationship with the vast majority of land plants. For agronomists the most important are the endomycorrhizal fungi that produce treeshaped branched structures called arbuscules inside the cortex of most crop plants. Evidence steadily accrued that established their importance in supplying the essential element phosphorus to plants but the availability of mineral fertilizers, such as superphosphate, caused many to assume that the contribution from mycorrhiza was unnecessary and even in fertile soils the organisms were more like parasites than partners of their hosts. But eventually there came the realization that arbuscular mycorrhiza provided far more services than supplying phosphorus. The recent appreciation of the biological functional diversity. The contribution of Clarisse Brìgido in developing the chapter discussing the complexity of functional diversity in AMF was also critical and she too has been of incalculable help and support. We are extremely grateful to Sabaruddin Kadir and Luis Alho, who generously provided material used in Chapter 5, as well as provided important feedback on the contents.